2006
DOI: 10.1007/s10397-006-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

Fertility rates after hysteroscopic treatment of submucous myomas depending on their type

Abstract: Patients' age and type of infertility (primary or secondary) are factors that do not affect fertility rates after hysteroscopic myomectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…We found that the results are best with type 0 fibroids-33.3% and the rates drastically fell with increasing intramural extension. The reduction in fertility rates with increasing intramural extension was also reported in a study by Ioannis et al .,[9] It was a small study that looked at 25 patients. They found a fertility rate of 57.15% in type 0, 42.8% in type 1, and 25% in type 2 fibroids.…”
Section: Discussionsupporting
confidence: 66%
“…We found that the results are best with type 0 fibroids-33.3% and the rates drastically fell with increasing intramural extension. The reduction in fertility rates with increasing intramural extension was also reported in a study by Ioannis et al .,[9] It was a small study that looked at 25 patients. They found a fertility rate of 57.15% in type 0, 42.8% in type 1, and 25% in type 2 fibroids.…”
Section: Discussionsupporting
confidence: 66%
“…A retro-* * * spective study found that the pregnancy rate was 33.8% after hysteroscopic resection of submucous fibroid, with 50% live births, 41.6% spontaneous abortions, and 8.4% fetal losses. The time from hysteroscopy to conception was 9.9 months, while the postoperative follow-up was 28.7 months [14]. Spontaneous abortion rate in the first trimester of pregnancy was 6% after hysteroscopic polypectomy and there was no statistical difference between patients with small or larger polyps [15].…”
Section: Discussionmentioning
confidence: 95%
“…Delivery at term was achieved by 35.7% of patients with type 0 myoma, by 28.5% of patients with type I myoma, and by 25% of patients with type II myoma, after hysteroscopic myomectomy. 13 Other studies also concluded that hysteroscopic leiomyoma resection also improves fertility rates, especially when tumors are the sole cause of infertility. [14][15][16] Even uterine artery embolization is an angiographic interventional procedure that delivers particulate emboli into both uterine arteries.…”
Section: Discussionmentioning
confidence: 99%